Optimization of second harmonic generation of gold nanospheres and nanorods in aqueous solution: the dominant role of surface area. Issue 4 (11th January 2016) - Ngo, Hoang Minh; Nguyen, Phuong Phong; Ledoux-Rak, Isabelle
Abstract : Gold nanoparticles display exceptionally strong β values. We demonstrated that the first hyperpolarizability ( β ) strongly depends on surface area of gold nanoparticles. Abstract : Size and shape of gold nanoparticles (AuNPs) have a strong influence on their second order nonlinear optical properties. In this work, we propose a systematic investigation of surface and shape effects in the case of small gold nanoparticles. Colloidal solutions on AuNPs with different sizes and shapes have been synthesized, i.e. nanospheres (diameters 3.0; 11.6; 15.8; 17.4; 20.0 and 43 nm) and nanorods (aspect ratios 1.47; 1.63 and 2.30). The first hyperpolarizability β values of these AuNPs have been measured by harmonic light scattering (HLS) at 1064 nm. For nanospheres and nanorods, we found that their β values are governed by a purely local, dipolar contribution, as confirmed by their surface area dependence. As an important consequence of these surface effects, we have revisited the previously reported aspect ratio dependence of β values for gold nanorods, and evidenced the predominant influence of nanoparticle area over aspect ratio considerations.